PRINSIP-PRINSIP MANAJEMEN VS KINERJA GURU: SEBUAH TINJAUAN UMUM - Sola, Ermi (Educational Leadership: Jurnal Manajemen Pendidikan, 2022)
Abstract: Principles of Management VS Teacher Performance: An Overview Education is an absolute necessity throughout life. Schools are formal educational institutions as one of the central points of education and learning. The quality of education in each school is different. This happens because of different managerial strategies in managing school resources. The quality of the education and learning process can be viewed from two aspects, namely the quality of the components and the quality of school management. Although the supporting components such as the availability of adequate facilities and infrastructure and sufficient funds, if they are not managed "well" and "properly" according to the education and teaching program (school program) that has been established, it is certain that the objectives of education and teaching will not be achieved. achieved effectively. Therefore, management principles are important instruments that can reveal the extent of success or failure of teachers in achieving learning objectives and school programs. Abstrak: Prinsip-Prinsip Manajemen VS Kinerja Guru: Sebuah Tinjauan UmumPendidikan merupakan kebutuhan mutlak sepanjang hayat. Sekolah merupakan lembaga pendidikan formal sebagai salah satu titik pusat pendidikan dan pembelajaran. Kualitas pendidikan setiap sekolah berbeda-beda. Hal ini terjadi karena strategi manajerial yang berbeda dalam mengelola sumber daya sekolah. Kualitas proses pendidikan dan pembelajaran dapat ditinjau dari dua segi, yaitu kualitas komponen dan kualitas pengelolaan sekolah. Walaupun komponen-komponennya penunjang seperti tersedianya sarana dan prasarana yang memadai dan dana yang cukup, jika tidak dikelola dengan “baik” dan “tepat” sesuai program pendidikan dan pengajaran (program sekolah) yang telah ditetapkan, maka dapat dipastikan tujuan pendidikan dan pengajaran tidak akan tercapai secara efektif. Oleh karena itu prinsip-prinsip manajemen merupakan instrumen penting yang dapat mengungkap sejauh mana keberhasilan atau kegagalan para guru dalam pencapaian tujuan pembelajaran maupun program sekolah.